Developing Mathematical Modeling Tasks Using Parking Fee for Learning Mathematics - Riyanto, Bambang (Universitas Sebelas Maret, 2021)
The purpose of this study is to produce valid mathematical modeling tasks using parking fees for learning mathematical modeling in SMK. This study used a research development approach by Akker, Gravemeijer, McKenney and Nieveen. This research consists of 3 stages, namely analysis, design and evaluation. The analysis step was carried out by analyzing students, curriculum, vocational needs, context needed and mathematical modeling. The second step is design and product. The last step is a formative evaluation design which consists of self-evaluation, one-to-one, expert review, small group, and field test. The research only conducted self-evaluation, one-to-one, and expert review. Data analysis used descriptive walk through, expert commentary analysis, solution analysis and student comments to get a valid parking fee context mathematical modeling problem for learning mathematics. This research has produced mathematical modeling problems valid using the context of parking fees for mathematics learning in SMK. The results of this study suggest that it is important for teachers to design and implement mathematical modeling problems using interesting and meaningful real-world contexts in learning mathematics, further research is important to provide scaffolding for students in mathematical modeling problems for mathematics learning, finally, research and learning mathematical modeling crucial to be applied in the future.